Epulis - A need for Vigilant Radiographic Evaluation - Mohd Malik Afroz; Laxmikanth Chatra; Prashanth Shenai (Wolters Kluwer Medknow Publications, 2007)
Epulis is a relatively common gingival swelling and is often due to inflammation. It is seen more commonly in females. A careful clinical examination followed by thorough radiographic investigation is required to rule out lesions such as peripheral ossifying fibroma which depicts calcifications. Here we present three cases which have a relatively similar clinical picture but varied in there radiographic and histopathologic appearance. The management and post treatment follow up of the cases are also discussed in detail.